Development and Implementation of a Model Regional Information System for Vocational-Technical Education. Final Report. Vol. 1 - Tennessee Univ., Knoxville. Occupational Research and Development Coordinating Unit.; Tennessee Univ., Knoxville. Occupational Research and Development Coordinating Unit. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1976)
Volume 1 of the report, covering the period July 1, 1974 to December 31, 1975, describes project goals, phases of operation, procedures followed, and results. Three planning and development districts in Appalachia were involved: Tennessee, North Carolina, and Virginia (encompassing an 18 county area). Three principal project goals were: (1) to develop a model regional information system for vocational technical education, (2) to test that model, and (3) to determine the feasibility of regional research and development efforts for information systems in terms of sharing information across political and geographic boundaries, range and scope of information requests, and problems in tracking manpower. Phases of operation included development of information files, user inservice training, system operation, and system evaluation. Results of a 57-item needs assessment questionnaire given to 40 administrators (with 36 responding) are discussed, while a data collection section reports on the sources used and variables considered. Twenty-five administrators, participants in a two-day workshop, evaluated the model, concluding that the Regional Information System offers great potential as a planning tool for vocational-technical education. Rankings are presented in tabular form. Further implementation considerations and recommendations are discussed. (MW)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: OEG-0-74-1747.
ERIC Note: For volume 2, see CE 006 902.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Administrator Attitudes; Information Dissemination; Information Needs; Information Systems; Models; Needs Assessment; Program Descriptions; Program Development; Program Evaluation; Questionnaires; Regional Planning; Regional Programs; Tables (Data); Technical Education; Vocational Education; Appalachia; Reports, Research